Development of student activity sheets based on Science Literacy to Improve Primary School Student Learning Outcomes - Hasan, Hasan; Kune, Syarifuddin; Rahmawati, Rahmawati (Institut Agama Islam Negeri Palopo, 2022)
This study aims to develop valid, practical, and effective student activity sheets based on scientific literacy. This study uses Research and Development with a 4-D model design developed in four stages: defining, designing, developing, and disseminating. This study involved 36 grade VI elementary school students. Data collection techniques are observation to analyze product needs, questionnaires to determine the validity and practicality of the product, and tests to determine the product's effectiveness. The results showed that the development of student activity sheets based on science literacy in Electrical Energy learning was very valid, practical and effective. Material experts rated it very valid with a final score of 0.81. The results of the practicality of using the teacher and student questionnaires were 3.85, and the value of effectiveness validation using the observation sheet was 3.84 with an N-gain score of 0.75.